Effects of Black Garlic Extract Against Monosodium Glutamate-Induced Liver Damage in Rats: Macroscopic Studies - Maulina, Nora; Zachreini, Indra; Gholib, Gholib; Akmal, Muslim (AVERROUS: Jurnal Kedokteran dan Kesehatan Malikussaleh, 2025)
Monosodium glutamate (MSG) enhances flavor during food processing by providing an umami taste, but its metabolic by-products can cause liver injury. The liver is crucial for the metabolism of xenobiotics including glutamate. Black garlic, derived from fresh garlic (Allium sativum L.) through chemical reactions and heat treatment, may have hepatoprotective properties; however, studies are limited. This study assessed the hepatoprotective effects of black garlic extract (BGE) on MSG-induced liver damage. Twenty-five Wistar rats (Rattus norvegicus) were divided into five groups (n = 5): P0 (negative control); P1 (MSG group), 8 mg/kg MSG for 21 days; and P2, P3, and P4, receiving the same MSG protocol as P1 plus BGE doses of 200, 400, and 600 mg/kg body weight, respectively, for 16 days. After the experiment, rats were euthanized for liver tissue extraction. Although liver weights in the BGE-treated groups were lower than those in the MSG group, the difference was not statistically significant. These results indicated that a BGE dose of 200 mg/kg body weight mitigated MSG-induced hepatic damage. Further biochemical and histological studies are required to elucidate the mechanism of BGE's hepatoprotective action of BGE against MSG-induced hepatotoxicity.